PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI 4-5 TAHUN DI KOTA PALANGKA RAYA - Sri Wahyuni; Saudah; Aghnaita (Jurnal I TIBAR, 2022)
Emotional social development can be stimulated through learning at school by paying attention to the applicable curriculum. In the Child Development Achievement Level Standard, indicators of social-emotional development include (a) self-awareness (b) a sense of responsibility for self and others (c) prosocial behavior. This study aims to describe the socio-emotional development of early childhood 4-5 years in PAUD Tunas Harapan Palangka Raya. This research uses a descriptive qualitative approach. This study describes or describes the socio-emotional development of early childhood in PAUD Tunas Harapan Palangka Raya. Sources of research data are primary data and secondary data, primary data are class teachers, accompanying teachers, and 19 children. While the secondary data sources are: documentation in the form of RPPM, RPPH, assessment results, and photos of children's activities. The data collected in this study used the methods of observation, interviews, and documentation. The results showed that early childhood in PAUD Tunas Harapan Palangka Raya had different socio-emotional development. Of the 19 children, 9 children began to develop (MB), 10 children developed according to expectations (BSH) which included 3 indicators, namely 1) Self-awareness, 2) A sense of responsibility for oneself and others, and 3) Prosocial behavior.